Reproductive biotechnologies for the 21st century - Ugalde, Julio Ram?n (Cuban Journal of Agricultural Science, 2014)
The reproductive biotechnology includes techniques designed to produce and preserve the domestic animals and those that are in danger of extinction or already extinct. The purpose of this study is to make a brief review about the evolution of the reproductive biotechnology and the possibility of its application and development in an immediate future. Key words: biotechnology, reproduction, domestic animals